MODERN PROBLEMS OF MANAGEMENT IN HEALTHCARE - Panoyeva Niso Yuldashevna (Western European Studies, 2025)
This article is dedicated to the problems of healthcare management in Uzbekistan. It examines the internal environmental factors influencing the effective management of a medical organization
Keywords: management; healthcare; budget